2009
DOI: 10.1038/ejhg.2009.156
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evidence of a noncausal association between the X-chromosome inactivation pattern and thyroid autoimmunity: a twin study

Abstract: An increased frequency of skewed X-chromosome inactivation (XCI) is found in clinically overt autoimmune thyroid disease (AITD) compared with controls. Whether skewed XCI is involved in the pathogenesis of autoantibodies to thyroid peroxidase (TPOAb) in euthyroid subjects is unknown. To examine the impact of XCI on the serum concentration of TPOAb, we studied whether within-cohort and within-twin-pair differences in XCI are associated with differences in serum concentrations of TPOAb. A total of 318 euthyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
1
16
0
1
Order By: Relevance
“…Hansen and colleagues [234] indicate that the genetic influence on serum autoantibodies to thyroid peroxidase was greater in females (72%) than in males (61%). Interestingly, no significant association between X chromosome inactivation and anti-thyroid peroxidase antibodies was found in MZ twins, but an association was found with DZ twins [237], and another study has also indicated a higher incidence of X chromosome inactivation in female twins [238]. An interesting study by Phillips and colleagues [236] found a higher MZ (which was also higher in females) compared to DZ concordance for anti-thyroglobulin.…”
Section: Autoimmune Thyroid Disease (Aitd)mentioning
confidence: 88%
See 1 more Smart Citation
“…Hansen and colleagues [234] indicate that the genetic influence on serum autoantibodies to thyroid peroxidase was greater in females (72%) than in males (61%). Interestingly, no significant association between X chromosome inactivation and anti-thyroid peroxidase antibodies was found in MZ twins, but an association was found with DZ twins [237], and another study has also indicated a higher incidence of X chromosome inactivation in female twins [238]. An interesting study by Phillips and colleagues [236] found a higher MZ (which was also higher in females) compared to DZ concordance for anti-thyroglobulin.…”
Section: Autoimmune Thyroid Disease (Aitd)mentioning
confidence: 88%
“…An earlier study by Lawrence [47] reported a concordance of 30%, whereas a larger Finnish study indicated an MZ pairwise concordance of 12.3%, and a DZ pairwise concordance of 3.5%, based on cohorts of 4136 MZ and 9162 DZ twins [11]. Higher rates of [262] Male and female twins from opposite sex pairs had higher frequency of thyroid antibodies compared to MZ pairs [237] No significant association between X chromosome inactivation and anti-thyroid peroxidase antibodies in female MZ twins Significant association between X chromosome inactivation and anti-thyroid peroxidase antibodies in female DZ twins [263] Higher prevalence of autoantibodies in DZ compared to MZ twins [236] For anti-thyroglobulin: 50 concordance have been reported in an Australian twin cohort, based on a twin registry which contained 3808 pairs of twins as of 1980, when the study occurred [48]. A 0.4% RA prevalence was found in a final cohort of 186 twins in 1990, with MZ and DZ pairwise concordance being 21% and 0% respectively [48].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 93%
“…While SXCI occurrence was associated with the autoimmune diseases including autoimmune thyroid diseases [38-40], and systemic sclerosis [41], this phenomenon has been linked to development of a few of malignant solid tumours [33] in females. In 1999, Buller et al reported that patients with invasive ovarian cancer had an increased frequency of SXCI compared to those without a detectable fully malignant ovarian tumor [18].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, [117] 63.6% 3.6% [157] 35% 3% Ulcerative colitis [153] 6.3% 6.3% 0% 0% [154] 16% 3% [155] 14.3% 18.2% 4.5% 4.5% [156] 18.8% 18.8% 0% 0% [157] 16% 2% epigenetic modifications have been investigated, and XCI seems to play a role in clinical autoimmune thyroid diseases pathogenesis in women [134,135]. Moreover, the degree of XCI has been associated to anti-TPO antibodies levels in euthyroid subjects [135], and especially in DZ twins, while in MZ twin pairs became nonsignificant [135].…”
Section: Autoimmune Thyroid Diseasementioning
confidence: 99%